Albert Hauf i Valls: Una pasión filológica. - DE COURCELLES, DOMINIQUE (Scripta)
Starting from a historical and interpretative overview of philology as an integrative discipline of knowledge, we analyze Albert Hauf 's contribution to it, paying special attention to his edition of the Vita Christi by Sor Isabel de Villena.